Los guantes antivibratorios: ¿une avenida de prevención eficaz y aplicable? - Alice Turcot; Michel Lehoux (Universidade do Porto, 2016)
Wearing anti-vibration gloves is one of preventive measures recommended to reduce exposure to hand-arm vibration. But what do we know about the effectiveness of these anti-vibration gloves and about the workers' acceptance? One literature review has been carried out in Medline (PubMed) and EBSCOhost, for the period from 1970 to 2014. A field study with questionnaires and interviews was done involving 30 workers that were invited to wear two types of anti-vibration gloves, for a short period of time each.Twenty-three (23) questionnaires about comfort and drawbacks of wearing anti-vibration gloves were completed. Twelve (12) individual interviews were analysed. Both types of suggested gloves were considered uncomfortable and, according to several workers, they hindered the performance of the job. Furthermore, the literature review reveals that the effectiveness of the gloves to reduce vibrations is low. Reducing hand-arm vibration exposure by wearing anti-vibration gloves has not been demonstrated. For the workers, the major problems are related with a decreasing dexterity, a discomfort and a disturbance at performing their jobs.